Student Satisfaction Index in Midwifery Study Program of Faculty of Medicine Universitas Brawijaya - Kanthi Titissari; Bambang Supriyono; Ainul Hayat (Wacana Journal of Social and Humanity Studies, 2020)
Students satisfaction index was the purpose of research and to measure the satisfaction index on the service of Bachelor in Midwifery Study Program, researcher engaged students for respondents. This study was conducted quantitatively employing the survey method. The subjects of this study included 65 active students of the Bachelor in Midwifery Study Program, class of 2016, 2017, 2018. The aspects reviewed to determine student satisfaction on the service of the Bachelor in Midwifery Study Program were based on five satisfaction index dimensions (tangibles, reliability, responsiveness, assurance, empathy). This results indicated, that the student satisfaction index on the service of the department, with regard to the aforementioned 5 dimensions, identified as â€œquite satisfiedâ€. The service provided to the students was concluded as "good".